2020
DOI: 10.1371/journal.pone.0241636
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-specific antigen dynamics after neoadjuvant androgen-deprivation therapy and carbon ion radiotherapy for prostate cancer

Abstract: Background This study aimed to explain the dynamics of prostate-specific antigen (PSA) levels in patients with prostate cancer who were treated with carbon ion radiotherapy (CIRT) and neoadjuvant androgen-deprivation therapy (ADT). Methods Eighty-five patients with intermediate-risk prostate cancer who received CIRT and neoadjuvant ADT from December 2015 to December 2017 were analyzed in the present study. The total dose of CIRT was set at 51.6 Gy (relative biological effectiveness) delivered in 12 fractions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The correlation of clinical variables with OS was assessed via Cox regression analyses. Prognostic factors, for which p values were calculated as < 0.10, were evaluated using the multivariate stepwise Cox regression model [19]. A p value of < 0.05 was considered signi cant.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation of clinical variables with OS was assessed via Cox regression analyses. Prognostic factors, for which p values were calculated as < 0.10, were evaluated using the multivariate stepwise Cox regression model [19]. A p value of < 0.05 was considered signi cant.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation of clinical variables with OS was assessed via Cox regression analyses. Prognostic factors, for which p-values were calculated as <0.10, were evaluated using the multivariate stepwise Cox regression model (19). A p-value of <0.05 was considered significant.…”
Section: Methodsmentioning
confidence: 99%
“…Darwis NDM et al reported that the PSA bounce was observed in 55.7% of patients, out of which 97.6% experienced an increase of less than 2.0 ng/ml [22]. In our previous study, we investigated PSA kinetics after the combination of neoadjuvant ADT and sCIRT in 85 patients with prostate cancer in the intermediate-risk group [23]. In that study, PSA elevations above the nadir PSA plus 2 ng/ml occurred in eight cases, of which seven experienced spontaneous declines in the PSA level.…”
Section: Plos Onementioning
confidence: 98%